Model Analisis Pengaruh Citra Merek dan Harga terhadap Keputusan Pembelian Xiaomi Smartphone Pada Asia Ponsel Pekanbaru - Silvia Sari Sitompul (COSTING : Journal of Economic, Business and Accounting, 2019)
Mobile is not only used to communicate via telephone or sms, but consumers want more so that mobile features are increasingly diverse. Since the internet began to boom in Indonesia, the Internet has become a mandatory feature and has turned into a function in the cellphone itself besides being used for telephone and sms. So it is not surprising that cellphones with the lowest prices must fulfill three conditions, which can be used for telephone, SMS, and the internet. Our people are very thirsty for browsing, chatting, playing games and also for work. The internet has also become a basic necessity for every individual, because with the internet, humans have a lot of information. The internet is also useful for business, politics, economics and socializing.The purpose of this study is to find out and analyze the influence of Brand Image and prices on the purchase decision of Xiaomi Smartphone. The method used is multiple linear regression analysiswith a sample of 100 respondents. The research results show that the prices effect significant on Consumer decisions on Xiaomi Smartphone while brand image does not have aeffect significant on Consumer decisions on Xiaomi Smartphone Keywords: Brand Image, Features, Prices